Patient Care Quality Management through Transformational Leadership: Literature Review - Eko Murdianto; Marliani; Ernani Hadiyati; Eko Priyo Purnomo (Journal Of Nursing Practice, 2024)
Background: Leadership is a central aspect of the nursing management process, with nurses serving as front-line personnel in providing services to patients. Inadequate quality of care has a significant impact on high mortality rates and substantial cost burdens. Purpose: This study aims to explore the relationship between the transformational leadership style of nurse managers and the quality of patient care. Method: Literature search was conducted in five database journals covering various disciplines. Original research and peer-reviewed methods published in English were included in the review criteria. The initial search yielded 4397 articles and only 24 articles met the criteria for analysis. The review process used the PRISMA system guideline. Results: The results of literature from various articles reveal that factors influencing the quality of care included job satisfaction, non-compliance with standard drug administration, high staff turnover, stress and fatigue, and organizational commitment. Conclusions: There was a significant correlation between transformational leadership and the quality-of-care outcomes. This leadership style provided inspiration to nursing managers enhancing care quality to the best level. Further study needs to provide evidence of adoption and implementation transformational leadership style.